Review on the role of pidotimod in recurrent respiratory infections in children - Ganapathy, Sridhar; Bhatia, Rakesh; Nivangune, Kundan; Muchhala, Snehal; Jain, Rishi (Indian Journal of Child Health, 2019)
Background: Physiological immaturity of the immune system is the most common cause of recurrent respiratory infections (RRIs) in children. Drugs acting on the immunological pathways such as immunostimulants can be a very useful approach in the management of RRIs in children. Pidotimod (PDT) is an immunostimulant that acts on both innate and adaptive immunity. The immunostimulant activity of PDT has been firmly established in the management of RRIs in children with or without asthma. Objectives: This review was performed to summarize the available literature on the correlation of immunity and RRIs and current evidence of PDT in RRIs and pneumonia in children. Methodology: The literature search was performed in PubMed and Google Scholar databases using search terms such as pidotimod, children, RRIs, and pneumonia. Results: A total of 18 clinical studies with 10,704 children were included in this review. This includes 13 randomized controlled trials, two meta-analysis, and two observational studies. This review of current clinical evidence demonstrates that when added to the standard of care, PDT significantly reduces the number of recurrences of RRIs, severity, and duration of acute episodes in children and is safe in its prevention and treatment. This ultimately results in reduced visits to pediatric clinics and lesser absenteeism from school. It is also effective in improving the clinical outcomes in pneumonia patients. Conclusion: Pidotimod is effective and safe in the prevention and treatment of RRIs in children.